Water budget during ultra-endurance exercise - Rogers, G.; Goodman, C.; Rosen, C. (Medicine & Science in Sports & Exercise, 1997)
We examined water gains and water losses in a group of athletes after an ultra-endurance event. Thirteen male triathletes competed in a triathlon consisting of 21 km canoeing, 97 km cycling, and 42 km running. Water loss determinations included sweat rate (940 +/- 163 g.h-1), urine output (41 +/- 38 g.h-1), and respiratory water loss (88 +/- 10 g.h-1). Water gain measurements included water intake (737 +/- 137 g.h-1) and the water content of the food intake (10 +/- 7 g.h-1), and we estimated the water of metabolism for carbohydrate (49 +/- 5 g.h-1) and fat (41 +/- 5 g.h-1) and the water released after glycogen utilization (104 +/- 64 g.h-1). Total water gain averaged 940 +/- 160 g.h-1, while the total water loss averaged 1069 +/- 163 g.h-1. Body weight changed from 69.87 +/- 7.14 kg before the race to 66.65 +/- 6.75 kg after the race (-4.61 +/- 2.94%). The sum of the exogenous water gains and the endogenous water gains (940 g.h-1) replaced almost 90% of the total water loss (1069 g.h-1). The difference (1334 g) represented a loss of about 1.9% of the initial body mass (69.87 kg). The exogenous water gains alone (747 g.h-1) replaced about 70% of the total water loss, and the difference represented a loss of over 4% of the initial body mass. Because of the nature of the endogenous sources of water gain, the total amount of water gain almost replaces the total amount of water loss (difference approximately 12%) even in the presence of a reduction in body mass (> 4%).